Analyzing the liquidity of commercial banks in India: Study on different bankgroups - Kasana, Ekta; Singh, Renu; Sahoo, Bibhu Prasad (The Economics and Finance Letters, 2024)
The present study investigates how macroeconomic and bank-specific determinants affect the liquidity of public, private, and foreign banks in India. Bank liquidity is crucial for maintaining financial stability, supporting economic growth, and preserving public trust in the banking system. Bank liquidity is critically significant for bank success. Since 2008, this study has taken 49 banks for analysis purposes. We have employed the fixed and random effect models to examine the impact of bank-specific and macroeconomic variables on the liquidity of diverse bank groups. The results show that deposits and capital have a positive influence, whereas interest rate, statutory liquidity ratio, and cash reserve ratio negatively influence public, private, and foreign banks. Profitability has an insignificant effect on all types of banks. Gross domestic product has a positive, significant influence on public and private banks, but an insignificant impact on foreign banks. Bank size significantly impacts private banks, whereas it has negligible influence on other banks. The findings can assist bank managers, policymakers, and academics in formulating policies that maintain bank liquidity without incurring any losses or undefined costs. The present research is useful for other countries with a similar economic framework, like India, to improve their bank liquidity structure.